UPAYA GURU TAHFIZ DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR’AN SISWA DI MADRASAH ALIYAH - SITI ISTIQOMAH; MU’IZATIN MAULIDIYAH (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study was to determine the efforts of tahfiz teachers in improving students' ability to memorize the Qur'an at MA Al-Karimi Gresik. This study uses qualitative research, with data collection techniques in the form of observation, interviews, and documentation, and uses data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the efforts needed to improve the student's ability to memorize the Qur'an at MA Al-Karimi include the following; 1) Correcting student reading, such as the length and short, 2) Providing examples of reading, namely with the teacher first reading verse by verse then followed by the students, 3) Providing motivation, such as giving encouragement and advice to students, 4) Inviting or guiding students to continue muraja'ah, 5) Using various methods, such as Talaqqi, tahfiz and takrir.